Adsorption of Chromium Ion by Acid Activated Low Cost Carbon-Kinetic, Mechanistic, Thermodynamic and Equilibrium Studies - S. Arivoli; M. Hema; M. Karuppaiah; S. Saravanan (E-Journal of Chemistry)
A carbonaceous adsorbent prepared from an indigenous waste by acid treatment was tested for its efficiency in removing chromium ion. The parameters studied include agitation time, initial chromium ion concentration, carbon dose, pH and temperature. The adsorption followed first order reaction equation and the rate is mainly controlled by intra-particle diffusion. Freundlich and Langmuir isotherm models were applied to the equilibrium data. The adsorption capacity (Qm) obtained from the Langmuir isotherm plots were 27.40, 26.06, 26.06 and 26.17 mg/g respectively at an initial pH of 7.0 at 30, 40, 50 and 60°C. The temperature variation study showed that the chromium ion adsorption is endothermic and spontaneous with increased randomness at the solid solution interface. Significant effect on adsorption was observed on varying the pH of the chromium ion solutions. Almost 70% removal of chromium ion was observed at 60°C. The Langmuir and Freundlich isotherms obtained, positive ∆H0 value, pH dependent results and desorption of dye in mineral acid suggest that the adsorption of chromium ion on PDC involves physisorption mechanism.